2016
DOI: 10.1080/1061186x.2016.1207648
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of R3V6 peptide-mediated delivery of an anti-microRNA-21 antisense-oligodeoxynucleotide in a glioblastoma animal model

Abstract: MicroRNA-21 (miR-21) expression in glioblastoma inhibits the expression of pro-apoptotic genes, thereby promoting tumor growth. A previous study showed that the amphiphilic R3V6 peptide is an efficient carrier of the anti-miR-21 antisense oligodeoxynucleotide (antisense-ODN) into cells in vitro. In the current study, in vivo delivery of antisense-ODN using the R3V6 peptide was evaluated in a glioblastoma animal model. In vitro transfection showed that the R3V6 peptide delivered antisense-ODN more efficiently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The amphiphilic R3V6 peptide is a good carrier in vitro and in vivo for the delivery of anti-miR-21 in glioblastoma. The authors recorded low tumor growth following intratumoral injection of the antimiR-21/R3V6 complex, compared with the antimiR-21/PEI25k and scrambled-antisense/R3V6 compounds [104].…”
Section: Peptidesmentioning
confidence: 99%
“…The amphiphilic R3V6 peptide is a good carrier in vitro and in vivo for the delivery of anti-miR-21 in glioblastoma. The authors recorded low tumor growth following intratumoral injection of the antimiR-21/R3V6 complex, compared with the antimiR-21/PEI25k and scrambled-antisense/R3V6 compounds [104].…”
Section: Peptidesmentioning
confidence: 99%
“…AMOs form together with their target miRNAs RNA duplexes which lead to the degradation of miRNAs by RNAse H. In order to function in vivo, AMOs require chemical modifications like 2′-O-methoxyethyl and phosphorothioate. Oh et al showed that by administering anti-miR-21 antisense oligodeoxynucleotide carrier by R3V6 peptide which has amphiphilic properties, directly in the glioblastoma of a xenograft animal model, the apoptosis of tumor cells was restored and consequently tumor growth was blocked [74].…”
Section: Mirnas As Potential Therapeutic Toolsmentioning
confidence: 99%
“…In addition to cultured glioma cells [ 87 , 249 ], several studies attempted miR-21 inhibition in established intracranial GBM, using various antagomiRs and delivery techniques. For example, injections of the miR-21 antisense-ODN complex with amphiphilic R3V6 peptide suppressed tumor growth of C6 glioma [ 250 ]. A selective small molecule inhibitor of miR-21 maturation (AC1MMYR2), when injected intraperitoneally to mice bearing orthotopic U87 tumors inhibited tumorigenesis [ 251 ].…”
Section: Microrna Normalization By Otmentioning
confidence: 99%